Quo vadis, perovskite emitters? - Sum, Tze Chien (2020)
Halide perovskites hold great promise for next generation printable optoelectronic devices. Within a decade of their debut in photovoltaics, these amazing materials proliferate beyond solar cells to applications such as light-emitting devices, lasers, radiation detectors, and memristors. Such versatility stems from perovskites’ favorable optoelectronic properties that are highly exceptional for a facile solution-processed system. Halide perovskite emitters have made significant inroads, in particular, perovskite light emitting device (PeLED) efficiencies have risen from <1% to >20% within 5 years, and perovskite continuous wave amplified spontaneous emission has also been demonstrated recently. This perspective distills the photophysical mechanisms underpinning the various approaches in enhancing their radiative efficiencies. Selected works are highlighted to detail the milestones and to chart the direction the field is heading. Challenges and opportunities for solid-state PeLEDs are discussed. A clear understanding of their basic photophysics and structure-function relations holds the key to rationalizing strategies and streamlining efforts to realize high efficiency PeLEDs and perovskite lasers.